Perhitungan Premi Tunggal Bersih pada Asuransi Jiwa Kredit Sinking Fund - Gatot Riwi Setyanto (Inferensi, 2022)
Various types of banking product innovations were rolled out to keep up with the needs and more advanced developments, one of which is a credit or loan facility that can be utilized by the public. This credit facility is in great demand by the public because it is very helpful, especially in terms of additional capital. However, this credit activity can also be full of risks because most of the funds are entrusted to the public. Therefore, the provision of credit must be accompanied by strict risk management. As time goes on after credit is realized, banks are faced with credit risk problems, namely bad credit. Conducting a 5C (Character, Capacity, Capital, Economic Condition, and Collateral) analysis of customers is one way for banks to reduce the risk of bad credit. In fact, even though anticipatory steps have been taken by applying the 5C analysis, there is still a risk of default due to the death of the debtor, which causes the loan to not be fully paid off. In response to the possibility of the foregoing, financial/banking institutions adopted a policy requiring debtors to obtain term life insurance for a period of time equal to the term of the loan. For this reason, banks usually cooperate with life insurance institutions. Therefore, it must be ensured that the net single premium is paid at the beginning of the credit loan. With regard to the above, this paper will provide an overview and also discuss the concept of calculating the net single premium on credit life insurance, especially for debtors who make loan transactions to banking institutions that apply loan repayments with the sinking fund concept with a period according to the loan repayment tenor. So that when the debtor dies, he can pay the remaining unpaid loan to the lending institution or  bank.